Comparing the effect of modeled climatic variables on the distribution of African horse sickness in South Africa and Namibia. Issue 2 (December 2015) - Liebenberg, Danica; van Hamburg, Huib; Piketh, Stuart; Burger, Roelof
ABSTRACT: Africa horse sickness (AHS) is a lethal disease of horses with a seasonal occurrence that is influenced by environmental conditions that favor the development of Culicoides midges (Diptera: Ceratopogonidae). This study compared and evaluated the relationship of various modeled climatic variables with the distribution and abundance of AHS in South Africa and Namibia. A comprehensive literature review of the historical AHS reported data collected from the Windhoek archives as well as annual reports from the Directorate of Veterinary services in Namibia were conducted. South African AHS reported data were collected from the South African Department of Agriculture, Forestry, and Fisheries. Daily climatic data were extracted for the time period 1993–2011 from the ERA‐interim re‐analysis dataset. The principal component analysis of the complete dataset indicated a significant statistical difference between Namibia and South Africa for the various climate variables and the outbreaks of AHS. The most influential parameters in the distribution of AHS included humidity, precipitation, evaporation, and minimum temperature. In South Africa, temperature had the most significant effect on the outbreaks of AHS, whereas in Namibia, humidity and precipitation were the main drivers. The maximum AHS cases in South Africa occurred at temperatures of 20–22° C and relative humidity between 50–70%. Furthermore, anthropogenic effects must be taken into account when trying to understand the distribution of AHS.